Expression of D-type cyclins in mantle cell and diffuse large B-cell lymphomas - Zlamalikova, Lenka; Moulis, Mojmír; Šálek, David; Jarkovský, Jiří; Šmarda, Jan; Šmardová, Jana (Oncology reports, 2016)
D-type cyclins are involved in cell cycle regulation and play an important role in the pathogenesis of lymphomas. Aberrant expression of cyclin D1 is associated with mantle cell lymphoma (MCL) and serves as a diagnostic marker of MCL. Analysis of cyclin D expression in tumor tissues of patients with diffuse large B-cell lymphoma (DLBCL) which comprises a heterogeneous group of tumors may contribute to their stratification. We analyzed expression of cyclin D1, D2, and D3 mRNAs in 30 MCL and 104 DLBCL patients using qRT-PCR and addressed their significance for disease outcome. We confirmed a high level of cyclin D1 mRNA in 29 MCL cases (97%). One case (3%) was identified as positive for cyclin D2. Expression of cyclin D1 was limited to MCL and did not occur in DLBCL. Overexpression of cyclin D2, which is rare in MCL, occurred more frequently in DLBCL (11 cases, 10.6%). We showed that high expression of cyclin D2 in DLBCL cases de novo decreased the overall survival rate (P=0.016) and progression-free survival (P=0.009). The expression pattern of cyclin D3 was similar in both types of studied lymphomas and it did not affect the disease outcome.
Keywords: exprese genu; difúzní velkobuněčný B-lymfom; Aged; Gene Expression; lidé středního věku; senioři; Biomarkers, Tumor; cyklin D; lidé; Middle Aged; Cyclin D; Kaplan-Meier Estimate; nádorové biomarkery; Female; Lymphoma, Large B-Cell, Diffuse; Male; ženské pohlaví; Lymphoma, Mantle-Cell; Humans; mužské pohlaví; Kaplanův-Meierův odhad; lymfom z plášťových buněk